Factors influencing effective smart learning environment in Malaysian universities - Ghani, Erlane; Muhammad, Kamaruzzaman; Ali, Mazurina Mohd; Johari, Razana Juhaida; Sukmadilaga, Citra (Journal of Asian Scientific Research, 2023)
This study aims to examine the factors influencing an effective smart learning environment in the universities in Malaysia from the perspective of the students. Specifically, this study examines three key factors: students’ attitudes towards smart learning, their perception of smart learning tools, and the impact of course design in the smart learning environment. This study utilized a quantitative approach using a questionnaire survey that was administered to a sample of 386 students enrolled in both private and public institutions without regard to their academic year. This study demonstrates that there exists a positive and statistically significant correlation between all three parameters and the efficacy of smart learning environments. These results suggest that institutions should consider the viewpoint of students when developing a smart learning environment. Ultimately, this has the potential to enhance their educational experience. This study’s findings offer additional insights into the various factors that can impact the efficacy of smart learning environments. These insights can aid universities in formulating strategies to optimize the content, activities, and assessments within such environments, thereby enhancing their overall effectiveness.